The eye lens dose of the interventionalist: Measurement in practice. (August 2022) - Meijer, E.J.; van Zandvoort, D.W.H.; Loos, M.J.A.; Tseng, C.M.E.S.N.; van Pul, C.
Highlights: A strong correlation between eye lens dose, Hp(3), and surface dose, Hp(0, 07). The personal dosimeter can be used to monitor the eye lens dose. Consistent results between three interventionalist groups Abstract: Objective: Early 2018, the new eye lens dose limit of 20 mSv per year for occupational exposure to ionising radiation was implemented in the European Union. Dutch guidelines state that monitoring is compulsory above an expected eye lens dose of 15 mSv/year. In this study we propose a method to investigate whether the eye lens dose of interventionalists would exceed 15 mSv/year and to determine if the eye lens dose can be derived from the regular personal dosimeter measurements. Methods: The eye lens dose, Hp(3), of interventional radiologists (n = 2), cardiologists (n = 2) and vascular surgeons (n = 3) in the Máxima Medical Centre, The Netherlands, was measured during six months, using thermoluminescence dosimeters on the forehead. Simultaneously, the surface dose, Hp(0, 07), and whole body dose, Hp(10), were measured using regular dosimeters outside the lead skirt at chest level. The dosimeters were simultaneously refreshed every four weeks. The eye lens dose was compared to both the body-worn dosimeter values. Measurements were performed in the angiography suite, Cath lab and hybrid OR. Results: A clear relation was observed between the two dosimeters: Hp(3) ≈ 0, 25 Hp(0, 07). The extrapolated year dose for the eye lens did not exceed 15 mSv for any of the interventionalists (average 3 to 10 studies/month). Conclusions: The eye lens dose can be monitored indirectly through the regular dosimeter at chest level. Additionally, based on the measurements we conclude that all monitored interventionalists remain below the dose limit and compulsory monitoring limit for the eye lens dose.